Experimental investigations for assessing the influence of fly ash on the flow through porous media in Darcy regime - Abhishish Chandel (IWA Publishing, 2021)
Hydraulic conductivity plays a vital role in the studies encompassing explorations on flow and porous media. The study investigates the compaction characteristics of a river sand (Beas, Sutlej, and Ghaggar rivers) and fly ash mix in different proportions and evaluates four empirical equations for estimating hydraulic conductivity. Experiments show that an increase in the fly ash content results in a decrease in the maximum dry density (MDD) and an increase in the corresponding optimum moisture content (OMC) of sand–fly ash samples. MDD at optimum fly ash content was achieved at low water content, which resulted in less dry unit weight than that of typical conventional fill. In Beas, Sutlej, and Ghaggar sands the optimum fly ash content up to which the hydraulic conductivity value reduced uniformly was found to be 30, 45, and 40%, respectively. Any further increase in the fly ash content results in a negligible decrease in hydraulic conductivity value. The observed hydraulic conductivity of sand–fly ash mix lies in the range of silts, which emboldens the use of sand–fly ash mix as embankment material. Further, the evaluation of empirical equations considered in the study substantiates the efficacy of the Terzaghi equation in estimating the hydraulic conductivity of river sand-fly ash mix.